PENGEMBANGAN MEDIA PEMBELAJARAN IPS BERBANTU MULTIMEDIA BERBASIS HERITAGE UNTUK MENINGKATKAN HASIL BELAJAR PADA SISWA SMP NEGERI KOTA MADIUN - Khoirul Huda (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2016)
The development of modern utilization of diverse applications today are quite varied and gives educators the opportunity to design a teaching component particularly interesting learning media. But regarding utilization rarely seen in junior Madiun. Based on observations obtained information that a lack of media development utilization of multimedia components and aspects of the material has not yet exploiting the potential of the surrounding environment for learning resources. The aim of research to develop multimedia media heritage until a prototype that has been tested media. This type of research is R & D. The research concludes that the scale is expanded in SMPN 6 Madiun showed a significant difference before and after applied multimedia heritage. Proven grades pre-test and post-test 64.64 93.21 to 0.05 then tested statistical models Paired Samples T Test. Respect of the rules of statistical hypothesis value of these calculations is <0.05, then rejected. Conclusion The hypothesis is accepted that there is a significant increase in student scores before and after a given multimedia heritage. It can be concluded that developed media effectively to improve student learning outcomes.Keywords: Development, Multimedia, Heritage, IPS